The First Record of the Subfamily Aenictinae (Hymenoptera, Formicidae) from Iran - Radchenko, A.G.; Alipanah, H. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Aenictus dlusskyi Arnoldi, 1968, представитель подсемейства Aenictinae, впервые приведен для фауны Ирана. Собранный материал сравнен с типами двух близких видов: A. dlusskyi и A. rhodiensis Menozzi. Показаны различия между этими видами. Aenictus dlusskyi Arnoldi, 1968, the member of the subfamily Aenictinae, is recorded for the first time from Iran. Collected material was compared with the types of two closely related species, A. dlusskyi and A. rhodiensis Menozzi. Differences between these species are shown.